The geographical context and its influence in the sociocultural life of the andean man - Lugo-Villegas, Ido (2020)
The main objective of the research was to determine the influence of the geographical context on the character and socio-cultural life of the Andean man, for which the descriptive, historical-dialectical and analytical-synthetic methods have been used. The main result of the research is that the geographical context: natural regions, ecological floors, orography, climatology, fauna, flora, hydrography influence the character and social, cultural, psychological, religious, economic and educational life of the Andean man. The results of the systematic observation carried out by means of the application of field diaries, notebook of notes and structured records of bibliographic analysis, show that the geographical context: natural regions, ecological floors, orography, climatology, fauna, flora, hydrography influence the character and in the daily life of the people of the stays, villages, hamlets, towns, communities and rural populated centers of the Andean areas of the province of Huánuco; The heterogeneous geographical context does not determine the social economic situation of the population in terms of development or underdevelopment of people from a scientific perspective. Within the conclusions reached we can affirm that the geographical context as a scenario and habitat of man, is the fundamental and indispensable basis for the development of the economic base (agriculture, livestock, mining, industry, commerce, tourism, transport) and the superstructure (social, cultural, psychological, religious, economic and educational). The geographical context and the natural and environmental elements of the environment do not condition the development or underdevelopment of society; that depends on public policies or government and state systems.Keywords: geography, social, cultural.